PENYULUHAN DENGAN MEDIA VIDEO EDUKASI EFEKTIF MENINGKATKAN PENGETAHUAN PEMBERANTASAN SARANG NYAMUK DEMAM BERDARAH DENGUE PADA SISWA SEKOLAH DASAR - Winda, I Gusti Ayu Putu; Sudiadnyana, I Wayan; Jana, I Wayan; Aryasih, I Gusti Ayu Made (Poltekkes Kemenkes Denpasar, 2024)
Students at SD Negeri 29 Pemecutan do not all know about efforts to eradicate dengue hemorrhagic fever mosquito nests. The purpose of this study was to determine the effectiveness of counseling using educational videos to increase knowledge of dengue mosquito nest eradication. The Pre-Experimental Design model with the One-Group Pretest-Posttest Design method was used in this research design. The results of the study were tested with paired t-tests, obtained p values (0.000) alpha (0.05), then H0 was rejected and Ha was accepted, so there was a difference in the average knowledge before counseling and after counseling on dengue mosquito nest eradication with educational videos for SD Negeri 29 Pemecutan students.